Effects of Bank Lending Rate on the Financial Performance of Deposit Money Banks in Nigeria - Adisa Omotayo Ikotun; Samson Adeyemi Ogundipe; Kolade Akinpelu Ayobami; Comfort Olaitan Bamidele (NDA Journal of Management Sciences Research, 2021)
This study analyzed the effects of bank lending rates on the financial performance of deposit money banks in Nigeria. The study used Prime Lending Rate as a proxy for Bank Lending Rate while Return on Assets (ROA), Return on Equity (ROE), and Net Interest Margin (NIM) were used as proxies for financial performance. The study used audited financial reported of five (5) banks quoted on the Nigerian Stock Exchange (NSE) from 2010 to 2019. Data collected were analyzed using Descriptive Statistics and Panel Least Square Regression. The findings revealed that the prime lending rate had a positive significant relationship on Return on Equity and Net Interest Margin while it had a negative influence on return on Assets of the selected banks. The study recommends that there is a dire need for deposit money banks in Nigeria to strengthen their lending rate policy through efficient and effective regulation. Also, there should be strong and efficient regulatory oversight of banks in Nigeria by the Central Bank of Nigeria aimed at reducing the rate of non performance loans.
Keywords: Banks; Lending rate; Performance; Finance; Nigeria